SVD Entropy Reveals the High Complexity of Ecological Networks - Strydom, Tanya; Dalla Riva, Giulio V.; Poisot, Timothée (Frontiers in Ecology and Evolution, 2021)
Quantifying the complexity of ecological networks has remained elusive. Primarily, complexity has been defined on the basis of the structural (or behavioural) complexity of the system. These definitions ignore the notion of 'physical complexity', which can measure the amount of information contained in an ecological network, and how difficult it would be to compress. We present relative rank deficiency and SVD entropy as measures of 'external' and 'internal' complexity respectively. Using bipartite ecological networks, we find that they all show a very high, almost maximal, physical complexity. Pollination networks, in particular, are more complex when compared to other types of interactions. In addition, we find that SVD entropy relates to other structural measures of complexity (nestedness, connectance, and spectral radius), but does not inform about the resilience of a network when using simulated extinction cascades, which has previously been reported for structural measures of complexity. We argue that SVD entropy provides a fundamentally more 'correct' measure of network complexity and should be added to the toolkit of descriptors of ecological networks moving forward.